XXI Century: The philosophy of a minimally invasive Dentistry, what has been changed did what’s changed from the diagnosis to the treatment of dental caries? (Research, Society and Development, 2021)
Introduction: Dental caries is the most common disease worldwide and negatively influences people quality of life. With the advancement of research, the diagnosis of carious lesions and the use of materials and techniques has gained a more conservative character. Objective: To evaluate, through scientific evidence available in the literature, the current proposals for interventions and protocols for the treatment of caries, aiming at maximum preservation and minimum intervention in the dental structure. Methodology: Selection of articles in the databases, MEDLINE (Medical Literature Analysis and Retrieval Online System), PUBMED. From the keywords “caries”, “partial” and “removal”, 50 articles (2010 to 2021) were pre-selected. Following the inclusion and exclusion criteria, 17 articles were selected and analyzed according to the management of injuries, observing the severity, the degree of activity of the caries and the type of material and technique to be used. Results: Studies demonstrated a greater understanding of the evolution of caries, the establishment of a more careful diagnosis and the development of adhesive and bioactive materials have enabled minimally invasive treatments. Significant differences between total, partial and 2-step (stepwise) removal of carious tissue have been found, being that the total removal and in 2 steps increase the chances of injury and/or pulp communication. Conclusion: The evolution of adhesive materials and a greater understanding of the development of caries enables the use of techniques and materials that guarantee less intervention and greater clinical success.